Comparative analysis of three histological fixative solutions in the trachea and small intestine of Mus Musculus (Linnaeus, 1758) "albino mouse" - Dávila-Robles, Miguel (2024)
The main objective of tissue preservation with the use of fixatives is to maintain the histology of an organ identical to its natural state for subsequent study. The most common fixatives used in histology are alcohol, formaldehyde, and Bouin's solution. Recent studies on the application of fixative substances in histological processes indicate the need to guarantee the quality of the relationship: type of fixator-sample. For this reason, the purpose of this work is to compare the fixation quality of alcohol, formaldehyde and Bouin's solution at the tissue level of the trachea and small intestine of Mus musculus (Linnaeus, 1758) "albino mouse". To do this, the animal was slaughtered using an anesthetic, then the samples were dissected, extracted and fixed, which were placed in vials containing ethyl alcohol, 10% formaldehyde and Bouin's solution for a week; Subsequently, the histological process methodology was followed. The results indicate that in the trachea, fixation with Bouin better preserves the cellular structure, including microvilli and glands, while alcohol and formaldehyde show less defined epithelia and differences in the submucosa. On the other hand, in the intestine, Bouin's solution better preserves the four histological layers, while alcohol and formaldehyde stand out in the preservation of microvilli and cell shape, although with variations in the submucosa. In short, it is necessary to use fixing mixtures, such as Bouin's solution, in order to enhance the qualities of each fixative and attenuate its defects and disadvantages.